Politics and the Courtroom: A Battle Between Federal Rule of Civil Procedure 24 and Amicus Curiae Briefs - Annie T. Stanford (Washington University Law Review, 2020)
Intervention under Rule 24 has been judicially construed in light of the 1966 Amendment to a loose burden far and away from its real-property-based origins. Recently, Rule 24 has been used in socially conscious ways to advance politico-ideological views about immigration and other important public interest issues. Following the Court’s decision in Town of Chester, intervenors who seek the same relief as an original litigant, a requirement that is easily satisfied in social justice cases, do not have to establish independent Article III standing and are thus treated as original litigants who may directly participate in a given litigation. This expansion has led to massive scale intervention. Massive scale intervention has occurred both through endless, debate-style filings of contentious intervention motions that crowd the stage of the original litigation, as well as through intervention by groups of hundreds of people, sometimes even styled as a class action of intervenors. Allowing standing and class action grouping through the backdoor of Rule 24 shortchanges and cuts the Court’s other long-standing doctrines off at the knees. If Rule 24 is left untethered, it will continue to interfere with the carefully crafted requirements of Article III standing and Rule 23 class actions. Should Rule 24 expand extra-jurisdictionally, additional res judicata and notice issues will arise. Rule 24 has been and will continue to be abused by politicians, special interest groups, and individual third parties on both sides of the political aisle. These perspectives are important, but are better suited for their traditional forum of amicus briefs. Courts should tighten the Rule 24 “significantly protectable interest” and “adequacy of representation” burden to intervene, and return politico-ideological perspectives on a given litigation to where they have traditionally thrived: in amicus briefs.
Keywords: Article III standing; Intervention; Federal rule of civil procedure 24; Amicus curiae brief; Amicus brief; Litigation; Town of Chester 137 S. Ct. 1645